ANALISIS PENGARUH CAPITAL, KUALITAS ASET, RENTABILITAS DAN SENSITIVITY TO MARKET RISKTERHADAP PROFITABILITAS PERBANKAN PADA PERUSAHAAN BUSN DEVISA DAN BUSN NON DEVISA - MUFIDATUR ROFIQOH, LINDA (Jurnal Ilmu Manajemen (JIM), 2014)
Abstract:The aims of this reaserch was to analyze the effectof capital, asset quality, earnings and sensitivity to market risk on bank profitability. This reasearch were analyzed using multiple linear regression .The result show that variable capital not significant to the profitability, because bank tend to be careful in investing their funds and greater emphasis on bank survival. Asset quality negative significant to the profitability,when NPL increase reserve the bank earning assets will fell, so that the suffered a financial loss. Rentability positive significant to the profitability, when NIM increase identifies the interest income on earning assets is high. Increase in interest income can be improving profitability. Sensitivity to market risk positive significant to the profitability, because when NOP down indicates the decline in foreign exchange earnings is smaller than the decrease in foreign exchange cost, thus can increasing profitability. Keywords:profitability, capital, asset quality, profitability and sensitivity to market risk.